Evaluating the ventilatory effect of transnasal humidified rapid insufflation ventilatory exchange in apnoeic small children with two different oxygen flow rates: a randomised controlled trial*. (22nd December 2020) - Riva, T.; Préel, N.; Theiler, L.; Greif, R.; Bütikofer, L.; Ulmer, F.; Seiler, S.; Nabecker, S.
Summary: Transnasal humidified rapid insufflation ventilatory exchange prolongs safe apnoeic oxygenation time in children. In adults, transnasal humidified rapid insufflation ventilatory exchange is reported to have a ventilatory effect with PaCO2 levels increasing less rapidly than without it. This ventilatory effect has yet to be reproduced in children. In this non‐inferiority study, we tested the hypothesis that children weighing 10–15 kg exhibit no difference in carbon dioxide clearance when comparing two different high‐flow nasal therapy flow rates during a 10‐min apnoea period. Following standardised induction of anaesthesia including neuromuscular blockade, patients were randomly allocated to high‐flow nasal therapy of 100% oxygen at 2 or 4 l.kg −1 .min −1 . Airway patency was ensured by continuous jaw thrust. The study intervention was terminated for safety reasons when SpO2 values dropped < 95%, or transcutaneous carbon dioxide levels rose > 9.3 kPa, or near‐infrared spectroscopy values dropped > 20% from their baseline values, or after an apnoeic period of 10 min. Fifteen patients were included in each group. In the 2 l.kg −1 .min −1 group, mean (SD) transcutaneous carbon dioxide increase was 0.46 (0.11) kPa.min −1, while in the 4 l.kg −1 .min −1 group it was 0.46 (0.12) kPa.min −1 . The upper limit of a one‐sided 95%CI for the difference between groups was 0.07 kPa.min −1, lower than the predefined non‐inferiority margin of 0.147 kPa.min −1 (p = 0.001). The lower flow rate of 2 l.kg −1 .min −1 was non‐inferior to 4 l.kg −1 .min −1 relative to the transcutaneous carbon dioxide increase. In conclusion, an additional ventilatory effect of either 2 or 4 l.kg −1 .min −1 high‐flow nasal therapy in apnoeic children weighing 10–15 kg appears to be absent.